Characterizing the boundary lateral to the shear direction of deformation twins in magnesium - Y. Liu (Nature Portfolio, 2016)
Twin propagation involves three-dimensional normal, forward and lateral motion of twin interfaces with respect to the twinning shear direction. Here, the authors combine electron microscopy and atomistic simulations to study the until now unknown lateral structure of tensile deformation twins in magnesium.